PREVALENCE, EVALUATION AND MANAGEMENT OF PREOPERATIVE ANAEMIA IN THE ELECTIVE GENERAL SURGICAL PATIENTS - Ali, Syed Asad; Soomro, Abdul Ghani; Memon, Amir Iqbal; Siddiqui, Akmal Jamal (Journal of Ayub Medical College Abbottabad, 2012)
Background: Anaemia is the commonest haematological problem in the preoperative patients. Often it is a sign of underlying disease or associated co-morbid condition. A low haemoglobin level is associated with an excess risk in surgical procedure and its outcome. Therefore an understanding of any cause, evaluation and any potential treatment is crucial in the preoperative setting. Our objective was to determine prevalence, evaluation and management of preoperative anaemia in the elective general surgical patients. Methods: Prospective observational study in Surgical Unit-II, Liaquat University Hospital Jamshoro from July 2008 to June 2009. One hundred and twenty-five anaemic cases were included in the study, with haemoglobin level <10 g/dl. Their age ranged from 13 to 70 years. They were evaluated for preoperative anaemia in relation to surgical problems and associated any co-morbid conditions. Results: Out of 830 patients during the study period, 125 patients were anaemic with haemoglobin level 2.1-9.9 g/dl. Fifty-six (44.8%) were male and 69 (55.2%) were female, and 68.5% patients were from rural areas. Hypochromic microcytic was seen in 101 (80.8%) cases. Commonest surgical problem associated with anaemia was malignancies (27.2%) followed by haemorrhoids (20%) and tuberculosis of abdomen (14.4%). Majority of patients (52%) were managed on oral iron supplements while 48% received blood transfusions. Keywords: Pre-operative, Anaemia, causes, evaluation, management, malignancy, haemorrhoids